2018
DOI: 10.12659/msm.911286
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Inertia in Type 2 Diabetes Patients in Primary Health Care Clinics in Central Bosnia

Abstract: BackgroundThe goal of this research was to determine the frequency of clinical inertia of general practice physicians in the region of Central Bosnia in healthcare for type 2 diabetes patients, to analyze characteristics of patients and physicians, as well as glucose regulation during clinical inertia, and, on the basis of these indicators, give recommendations for reducing clinical inertia.Material/MethodsThis study included 29 doctors, family physicians, or general practitioners, who collected data in a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The delayed diagnosis might be not related specifically to the presence of hypertension but probably to the determinants of the overall cardiovascular comorbidities. This is consistent with the results of a study in Bosnia, wherein the patients with high blood pressure and comorbidities had a higher risk of clinical inertia because physicians paid more attention to healthy patients and those who were thought to be more disciplined [ 24 ]. Additionally, a meta-analysis by Aujoulat et al showed that clinical inertia was more common in patients with comorbidities [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The delayed diagnosis might be not related specifically to the presence of hypertension but probably to the determinants of the overall cardiovascular comorbidities. This is consistent with the results of a study in Bosnia, wherein the patients with high blood pressure and comorbidities had a higher risk of clinical inertia because physicians paid more attention to healthy patients and those who were thought to be more disciplined [ 24 ]. Additionally, a meta-analysis by Aujoulat et al showed that clinical inertia was more common in patients with comorbidities [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with that of the study in the U.S., whereby physicians with less experience (<10 years of practice) provided appropriate diagnoses because they were updated with the guidelines and had recent publication knowledge [ 4 ]. Moreover, the study in Bosnia found that physicians not considering the clinical guidelines for treatment could cause delayed diagnosis [ 24 ]. Additionally, physicians with insufficient clinical knowledge provided inappropriate treatment caused by the misinterpretation of the guidelines or disagreement with guidelines that define HbA1c ≥6.5% as a diagnostic criterion but HbA1c <7% as the treatment goal [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…When these physicians are confronted in such situations, the phenomenon of “clinical inertia” is evident. It is referred to as “A consultation in which a change in treatment based on a diabetes-related variable was indicated but did not occur” [ 28 , 29 ]. This leads to inappropriate prescribing and improper use of these medications.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical inertia is defined as the failure to enhance drug therapy when clinically indicated [20]. The extent of clinical inertia in diabetes management ranges from 8.4 to 70%, depending on the research method and the country where the study was performed [21]. In the United States, the prevalence of clinical inertia ranges from 28 to 73% [22].…”
Section: Introductionmentioning
confidence: 99%